Olfactory function in migraine both during and between attacks. (October 2014) - Marmura, Michael J; Monteith, Teshamae S; Anjum, Waseem; Doty, Richard L; Hegarty, Sarah E; Keith, Scott W
Introduction: People with migraine often report being osmophobic, both during and between acute migraine attacks. It is not clear, however, whether such reports are associated with changes in olfaction such as hyperosmia, as measured by psychophysical testing. In this case-control study we quantitatively assessed olfactory identification ability, which correlates with threshold tests of olfactory acuity, in patients with migraine at baseline (no headache), during migraine episodes, and after a treated attack and compared the test scores to those of matched control subjects. Methods: Fifty episodic migraine subjects and 50 and sex- and age-matched controls without headache were tested. All completed the University of Pennsylvania Smell Identification Test (UPSIT), a standardized and well-validated olfactory test. Results: At baseline, the UPSIT scores did not differ significantly between the migraine and control study groups (median paired score difference: −1, p = 0.18). During migraine attacks, a minority of migraine subjects (eight of 42) developed microsmia (i.e. lower test scores by at least four points), suggesting that, as compared to their matched controls, olfactory acuity was somewhat impaired during migraine attacks ( p = 0.02). This difference was less pronounced and not statistically significant after a successfully treated attack ( p = 0.15). Discussion: People with episodic migraine were found to have similar olfactory function as age- and sex-matched controls, but a minority exhibit microsmia or hyposmia during acute attacks. The cause of this dysfunction is unknown, but could relate to autonomic symptoms, limbic system activation, or disorders of higher order sensory processing.